Cross-Border Cooperation Between Ukraine and Poland Under Condition of Financial Crisis - Shcherba, Halyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Article is devoted to the promotion of strategies of development of transborder cooperation in the Polish-Ukrainian border. In the paper defined the features and characteristics of transborder cooperation, factors enhance the infrastructure of transborder regions. The author focuses on the problems of European regions as a major component in the process of state support for cross-border cooperation.

Artykuł poświęcono strategii rozwoju współpracy transgranicznej między Polską a Ukrainą. Określono cechy charakteryzujące współpracę transgraniczną oraz czynniki determinujące rozwój infrastruktury w przygranicznych regionach. Uwagę skupiono na euroregionach, które są głównymi uczestnikami współpracy transgranicznej.